Robotics: Science and Systems XVII 2021
DOI: 10.15607/rss.2021.xvii.011
|View full text |Cite
|
Sign up to set email alerts
|

RMA: Rapid Motor Adaptation for Legged Robots

Abstract: Fig. 1: We demonstrate the performance of RMA on several challenging environments. The robot is successfully able to walk on sand, mud, hiking trails, tall grass and dirt pile without a single failure in all our trials. The robot was successful in 70% of the trials when walking down stairs along a hiking trail, and succeeded in 80% of the trials when walking across a cement pile and a pile of pebbles. The robot achieves this high success rate despite never having seen unstable or sinking ground, obstructive ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
110
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(125 citation statements)
references
References 34 publications
1
110
0
Order By: Relevance
“…Hwangbo et al [1] trained control policies for the ANYmal robot [2] for robust and high-speed locomotion while keeping the balance under large disturbances. In the later works [3] and [4], RL-trained policies made a quadrupedal robot traverse over various challenging terrains such as slippery ground, vegetation, and rocky terrain. They trained an encoder which compresses environmental information and enabled effective environmentaware locomotion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hwangbo et al [1] trained control policies for the ANYmal robot [2] for robust and high-speed locomotion while keeping the balance under large disturbances. In the later works [3] and [4], RL-trained policies made a quadrupedal robot traverse over various challenging terrains such as slippery ground, vegetation, and rocky terrain. They trained an encoder which compresses environmental information and enabled effective environmentaware locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…The existing control approaches for quadrupedal locomotion rely on accurately estimated state input [1], [3], [4], [7], [10]- [13]. However, we observed that existing This work was supported by Samsung Research Funding & Incubation Center for Future Technology at Samsung Electronics under Project Number SRFC-IT2002-02.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcement Learning (RL) techniques have been increasingly popular in training autonomous robots to perform complex tasks such as traversing uneven outdoor terrains [1] and navigating through cluttered indoor environments [2]. Through interactions with environments and feedback in the form of reward functions, robots learn to reach target locations relying on onboard sensing (e.g., RGB-D cameras).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous Sim-to-Real techniques do not explicitly address safety of the robots. Usually it is worth compromising the performance (e.g., success rate and time needed for reaching the target) to allow better safety of the system (e.g., rate of bumping into Email addresses: kaichieh@princeton.edu (Kai-Chieh Hsu), allen.ren@princeton.edu (Allen Z. Ren) 1 Equal contributions in alphabetical order 2 Equal contributions in advising Figure 1: Overview of the Sim-to-Lab-to-Real framework. Top: During Sim stage, we train robot policies in a wide variety of environments and conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation